Competition modulates buyers' reaction to sellers' cheap talk - Sander Onderstal; Shaul Shalvi; Ivan Soraperra (Tinbergen Institute, 2023)
Sellers in real-estate markets, on internet platforms, in auction houses, and so forth, routinely pose non-binding price requests. Using a laboratory experiment, we examine how competition moderates the way such cheap-talk communication affects trade between buyers and sellers. For bilateral trade, the literature has identified efficiency, anchoring, and granularity effects of cheap-talk communication on negotiation outcomes. Our results show that most of these effects survive with competition, although some of them become weaker. Our main findings are the following: (i) The ability of sellers to make non-binding price requests has a positive effect on efficiency in that it helps trading partners close marginal deals both in bilateral bargaining and in competition; (ii) Competition reduces the informativeness of the price requests and weakens the anchoring effect of the level of the price request; (iii) Sellers communicating more granular price requests attract more granular buyer bids; (iv) The granularity of the seller's price request does not impact the selling price.
Keywords: C72; C92; D91; 330; Cheap-talk communication; efficiency; anchoring; price granulatiry; laboratory experiment